Adsorption and gas-sensing properties of SF6 decomposition components (SO2, SOF2 and SO2F2) on Co or Cr modified GeSe monolayer: a DFT study. (March 2023) - Chen, J.; Jia, L.; Cui, X.; Zeng, W.; Zhou, Q.
Abstract: This paper first proposed to modify the GeSe monolayer by doping Co and Cr atoms and investigated the potential application in the monitoring SF6 insulation equipment. The adsorption mechanism of these three gases on Co/Cr-Gese monolayers is systematically studied based on density functional theory. The adsorption mechanism of three gas molecules on the new sensors (Co-GeSe and Cr-GeSe) was evaluated from the aspects of adsorption energy, charge transfer amount, energy band structure, molecular frontier orbital, and recovery time. The results show that Co and Cr modification can significantly improve surface activity of the intrinsic GeSe monolayer, which can make the intrinsic GeSe monolayer possess better absorption and sensing performance. Especially, the Cr-GeSe monolayer gets more sensitive to the target gas, indicating this monolayer has the prospect of becoming the adsorption material of the target gas (SO2, SOF2, and SO2 F2 ). The reasonable adsorption energy and large change of bandgap indicate that Co-GeSe monolayer can be a potential candidate for SO2 and SOF2 sensors. In addition, this work provides theoretical guidance for the further study of transition metal-doped GeSe monolayer for detecting the decomposition products of SF6 in the field of electrical engineering. Graphical abstract: The influence of transition metal atom (Co and Cr) doping on the structure parameters and electronic properties of GeSe monolayer was studied based on DFT calculations. We found Cr and Co atom doped GeSe monolayer exhibits excellent adsorption capacity to SF6 decomposition gases and the processes of absorption both are chemical. Image 1 Highlights: ▲The optimal structure of Cr-GeSe and Co-GeSe monolayer were obtained by the Co and Cr atom was absorbed above the TV site of pristine GeSe monolayer. ▲Co-GeSe and Cr-GeSe exhibits significantly good adsorption performance to SF6 decomposed species (SO2, SOF2 and SO2 F2 ). ▲The electrical conductivity changes and the band gap before and after gases adsorption were discussed to judge the type of SF6 decomposed species. ▲The desorption time shows the superior prospect as a gas adsorbent for Cr-GeSe.